2013
DOI: 10.1177/2048872613514013
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of tirofiban-supported primary percutaneous coronary intervention in patients pretreated with 600 mg clopidogrel: results of propensity analysis using the Clinical Center of Serbia STEMI Register

Abstract: Background: Studies with platelet glycoprotein IIb/IIIa receptor inhibitors (GPIs) showed conflicting results in primary percutaneous coronary intervention (PPCI) patients who were pretreated with 600 mg clopidogrel. We sought to investigate the short-and long-term efficacy and safety of the periprocedural administration of tirofiban in a largest Serbian PPCI centre. Methods: We analysed 2995 consecutive PPCI patients enrolled in the Clinical Center of Serbia STEMI Register, between February 2007 and March 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 56 publications
(61 reference statements)
1
28
0
Order By: Relevance
“…According to these studies, the 2012 ESC guideline defined that there is no definitive answer regarding the current role of the routine use of GP IIb/IIIa inhibitors in primary PCI in the era of potent DAPT, particularly when prasugrel or ticagrelor is used ( 5 ). On the other hand, recent studies ( 6 , 7 ) of tirofiban with DAPT in STEMI support the findings of Kaymaz et al ( 1 ) Tirofiban administered with primary PCI following the administration of 600 mg clopidogrel improved the primary efficacy outcome at 30-day and 1-year follow-up without an increase in major bleeding. Zhu et al ( 7 ) demonstrated that the upstream use of tirofiban is significantly associated with an increased incidence of spontaneous reperfusion and a decreased incidence of MACE at 30-day as well as 90-day follow-up in patients treated with primary PCI for STEMI.…”
supporting
confidence: 60%
“…According to these studies, the 2012 ESC guideline defined that there is no definitive answer regarding the current role of the routine use of GP IIb/IIIa inhibitors in primary PCI in the era of potent DAPT, particularly when prasugrel or ticagrelor is used ( 5 ). On the other hand, recent studies ( 6 , 7 ) of tirofiban with DAPT in STEMI support the findings of Kaymaz et al ( 1 ) Tirofiban administered with primary PCI following the administration of 600 mg clopidogrel improved the primary efficacy outcome at 30-day and 1-year follow-up without an increase in major bleeding. Zhu et al ( 7 ) demonstrated that the upstream use of tirofiban is significantly associated with an increased incidence of spontaneous reperfusion and a decreased incidence of MACE at 30-day as well as 90-day follow-up in patients treated with primary PCI for STEMI.…”
supporting
confidence: 60%
“…The Serbia STEMI Register study showed that tirofiban administration with PPCI, following pretreatment with 600 mg clopidogrel, improved the primary outcome after 30 days and after 1 year without an increase in major bleeding. [26] Consistent with the effect of tirofiban, other GP IIb/IIIa inhibitors such as eptifibatide and abciximab improve long-term outcomes in high-risk patients with AMI following PCI. Comparisons of the need for vascular access and major bleeding complications were not possible due to low rates of these events.…”
Section: Discussionmentioning
confidence: 89%
“…In the present study, data from the prospective Clinical Center of Serbia STEMI Register, for a subgroup of 2,436 consecutive patients, wo were hospitalized between February 2006 and October 2010, were used. The purpose of the prospective Clinical Center of Serbia STEMI Register has been published elsewhere ( 16 ). In brief, the objective of the register is to gather complete and representative data on the management and short- and long-term outcomes of patients with STEMI who have undergone primary PCI at the Center.…”
Section: Methodsmentioning
confidence: 99%